2007
DOI: 10.5006/1.3278329
|View full text |Cite
|
Sign up to set email alerts
|

Cold Work and Temperature Dependence of Stress Corrosion Crack Growth of Austenitic Stainless Steels in Hydrogenated and Oxygenated High-Temperature Water

Abstract: The rate of stress corrosion cracking (SCC) was measured for nonsensitized, cold-worked Type 316 (UNS S31600) and Type 304 (UNS S30400) in both hydrogenated pressurized water reactor (PWR) primary water and oxygenated water, each containing standard boron and lithium additions. First, the stress dependence of 5% to 20% cold-worked Type 316 (CW316) was determined in the PWR primary environment at 320°C. The rate of crack growth increased both with increasing cold work and stress intensity. Intergranular morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 18 publications
5
59
0
Order By: Relevance
“…The orientation of the deformation bands with respect to the propagation direction seems to play an important role. (7) No evidence for selective grain boundary oxidation ahead of the crack tip was found. However, enhanced oxidation was observed at the highly stressed regions around the crack tip.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The orientation of the deformation bands with respect to the propagation direction seems to play an important role. (7) No evidence for selective grain boundary oxidation ahead of the crack tip was found. However, enhanced oxidation was observed at the highly stressed regions around the crack tip.…”
Section: Discussionmentioning
confidence: 96%
“…Cold work has also been shown to change the grain boundary diffusion rates of the alloy constituents, due to the increase in the proportion of high-angle sub-boundaries, which are faster diffusion paths [38]. Arioka also found similar dependencies of SCC and creep on temperature, cold work and rolling direction, and suggested that creep by grain boundary diffusion plays a critical role in the growth of SCC [7].…”
Section: Influence Of Cold Work On the Deformation Microstructure Of mentioning
confidence: 86%
See 3 more Smart Citations